Size tunable elemental copper nanoparticles: extracellular synthesis by thermoanaerobic bacteria and capping molecules. Issue 3 (28th November 2014) - Jang, Gyoung Gug; Jacobs, Christopher B.; Gresback, Ryan G.; Ivanov, Ilia N.; Meyer, III, Harry M.; Kidder, Michelle; Joshi, Pooran C.; Jellison, Gerald E.; Phelps, Tommy J.; Graham, David E.; Moon, Ji-Won
Abstract : Elemental Cu nanoparticles in aqueous solution were synthesized by a biological process using anaerobic metal-reducing bacteria and chelator and capping molecules. Abstract : Bimodal sized elemental copper (Cu) nanoparticles (NPs) were synthesized from inexpensive oxidized copper salts by an extracellular metal-reduction process using anaerobic Thermoanaerobacter sp. X513 bacteria in aqueous solution. The bacteria nucleate NPs outside of the cell, and they control the Cu 2+ reduction rate to form uniform crystallites with an average diameter of 1.75 ± 0.46 μm after 3 days incubation. To control the size and enhance the air stability of Cu NPs, the reaction mixtures were supplemented with nitrilotriacetic acid as a chelator, and the surfactant capping agents oleic acid, oleylamine, ascorbic acid, orl -cysteine. Time-dependent UV-visible absorption measurements and XPS studies indicated well-suspended, bimodal colloidal Cu NPs (70–150 and 5–10 nm) with extended air-stability up to 300 min and stable Cu NP film surfaces with 14% oxidation after 20 days. FTIR spectroscopy suggested that these capping agents were effectively adsorbed on the NP surface providing oxidation resistance under aqueous and dry conditions. Compared to previously reported Cu NP syntheses, this biological process substantially reduced the requirement for hazardous organic solvents and chemical reducing agents, while reducing the levels of Cu oxide impurities in the product. This process was highly reproducible and scalable from 0.01 to 1 L batches.